The Effect of Work Ability and Professionalism on Employee Performance Through Additional Income at the Binjai City Tourism Office - Wira Juwita; Kiki Farida Ferine (International Journal of Society and Law, 2024)
The purpose of this study is to find out and analyze the influence of Work Ability and Professionalism on Employee Performance mediated by Additional Income at the Binjai City Tourism Office. This research was carried out at the Binjai City Tourism Office. The type of research is quantitative associative. The sample in this study is 38 employees with ASN and honorary status at the Binjai City Tourism Office. The sampling technique in this study uses a saturated sample where the entire population will be a sample in this study as many as 38 people. The results of the study show that Employability has a significant influence on Employee Performance as shown by a T-Statistic value of 7,311 > 1.96 and a P Value of 0.000 < 0.05. In the effect of Professionalism on Employee Performance, the T-Statistical value data was obtained from 5,570 > 1.96 and the P-Value value was 0.000 < 0.05 or there was an influence of Professionalism on Employee Performance. Workability has a significant effect on Employee Additional Income with a T-Statistic value of 2,401 > 1.96 with a P-Value of 0.002 < 0.05. Professionalism has no effect on Employee Additional Income. This can be seen from the results of the T-Statistic value of 0.668 < 1.96 with a P-Value of 0.548 > 0.05. In the effect of Additional Income on Employee Performance, a T-Statistic value of 3,701 > 1.96 was obtained with a P-Value of 0.009 < 0.05 which means that Additional Income has a significant effect on the Performance of Employees of the Binjai City Tourism Office. In the indirect influence, the results show that Additional Income does not have a role as an intervention variable in explaining the relationship between Work Ability and Professionalism on Employee Performance. This shows that improvements in Workability and Professionalism cannot increase Additional Income, which ultimately does not contribute to the improvement of the Performance of Employees of the Binjai City Tourism Office.Top of Form